The Effectiveness of Video and Booklet Media in HIV/AIDS Health Education for Adolescents: A Quasi-Experimental Study - Arihta Br. Sembiring; Novita Andriani Br. Manjorang (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Health education is an important strategy to improve HIV/AIDS prevention in adolescents, but the effectiveness of educational media can vary. This study aims to compare the effectiveness of video media and booklet media in HIV/AIDS health education in adolescents. The study used a quasi-experimental pretest–posttest design with a control group, involving 60 students (30 in each of the video media and booklet media groups). Knowledge, attitudes, and practices related to HIV/AIDS were measured before and after the intervention using a standardized questionnaire, and the data were analyzed to determine baseline equivalence and differences in outcomes between groups at pretest and posttest, with a significance level of 5%. The results showed that both groups had equivalent baseline means, indicated by no significant differences in the pretest knowledge (p=0.770), attitudes (p=0.802), and practices (p=0.715). After the intervention, the posttest mean knowledge of the video media group (86.03±4.916) was higher than that of the booklet media group (82.97±4.902) and was significantly different (p=0.019). In the attitude and action variables, the posttest mean of the video media group was also higher, but the difference was not significant (attitude: 84.73±5.595 vs 83.33±6.019; p=0.355; action: 84.67±5.713 vs 82.67±6.397; p=0.207). These findings indicate that both media are effective in improving post-intervention outcomes, with video media superior, especially in increasing knowledge. Conclusion: Video media is more effective than booklets in increasing HIV/AIDS knowledge in adolescents, while there is no significant difference in effectiveness between the two media in attitudes and actions Keyword: HIV/AIDS, adolescents, health education, video media, booklet, quasi-experimental